Kingdom of the Netherlands-Netherlands : Financial Sector Assessment Program:: Technical Note-Securities Supervision-Selected Issues Regarding the Regulators, Auditor Oversight, and Collective Investment Scheme Management. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations of the Financial Sector Assessment Program for the Netherlands regarding auditor oversight, collective investment fund management, and regulatory issues. The legal regime and the day-to-day supervision activities conducted by the Netherlands Authority for the Financial Markets and the Dutch central bank are extensive and consistent with international expectations. The approach to the supervision of the small but growing crowd-funding sector strikes a fair balance between enhancing innovation and protecting investors. The Dutch regime for audits and auditor oversight also complies with the expectations of the International Organization of Securities Commissions and appears to work well in practice.